Biodrying of Pulp and Paper Secondary Sludge: Kinetics of Volatile Solids Biodegradation - Huilinir-Curio, C (Elsevier Ltd, 2014)
This study focuses on the kinetics of volatile solids (VS) biodegradation of the biodrying process using pulp and paper secondary sludge. The experiments were carried out with air-flow rates of 0.51, 1.61, 3.25 and 5.26L/minkgVS) and initial moisture content of 64-66% w.b. Using five kinetic models and a nonlinear regression method, kinetic parameters were estimated and the models were analyzed with two statistical indicators. Higher air-flow rates cause greater moisture content reduction, lower temperature in the matrix, and lower VS reduction. At an air-flow rate as high as 5.26L/minkgVS there is no biodrying but only convective drying. The kinetic models used successfully simulate the VS biodegradation under biodrying conditions, with a root mean square error (RMSE) between 0.007929 and 0.02744. In conclusion, we show for the first time that VS biodegradation in the biodrying process can be successfully modeled with a kinetic model. © 2014 Elsevier Ltd.